Pausing of flagellar rotation is a component of bacterial motility and chemotaxis. - Lapidus, I R (1988)
When bacterial cells are tethered to glass by their flagella, many of them spin. On the basis of experiments with tethered cells it has generally been thought that the motor which drives the flagellum is a two-state device, existing in either a counterclockwise or a clockwise state. Here we show that a third state of the motor is that of pausing, the duration and frequency of which are affected by chemotactic stimuli. We have recorded on video tape the rotation of tethered Escherichia coli and Salmonella typhimurium cells and analyzed the recordings frame by frame and in slow motion. Most wild-type cells paused intermittently. The addition of repellents caused an increase in the frequency and duration of the pauses. The addition of attractants sharply reduced the number of pauses. A chemotaxis mutant which lacks a large part of the chemotaxis machinery owing to a deletion of the genes from cheA to cheZ did not pause at all and did not respond to repellents by pausing. A tumbly mutant of S. typhimurium responded to repellents by smooth swimming and to attractants by tumbling. When tethered, these cells exhibited a normal rotational response but an inverse pausing response to chemotactic stimuli: the frequency of pauses decreased in response to repellents and increased in response to attractants. It is suggested that (i) pausing is an integral part of bacterial motility and chemotaxis, (ii) pausing is independent of the direction of flagellar rotation, and (iii) pausing may be one of the causes of tumbling.